Colorectal tumors from APC*I1307K carriers principally harbor somatic APC mutations outside the A8 tract. - Peter Zauber; Timothy Bishop; Claire Taylor; Marlene Sabbath-Solitare; Stephen Marotta; Ian Tomlinson (PLoS ONE)
Purpose APC*I1307K (c.3920T>A) is an inherited variant associated with colorectal tumour risk found almost exclusively in those of Ashkenazi Jewish ancestry. A single nucleotide substitution creates an oligo-adenine tract (A8) that appears to be inherently prone to further mis-pairing and slippage. The reported multiple tumor phenotype of carriers is not easily reconciled with molecular and population genetics data. We postulated that some c.3920T>A carriers with multiple adenomas have other unidentified APC germ line or somatic mutations. Methods DNA from 82 colonic tumours and accompanying normal tissue collected from 29 carriers with multiple colorectal tumors was directly sequenced between codons 716 and 1604. We also assessed APC gene loss of heterozygosity. Results One patient (3.4%) was found to have an additional APC germ line mutation. Twenty-five of the tumours showed no significant somatic molecular change, 36 showed one change, 20 showed two, and one tumour showed more than 2 changes. Our data suggest a correlation between advancing histology and fewer beta-catenin binding sites remaining in the mutant proteins. Conclusions There were no other common germ line variants identified within the region of the APC gene examined, suggesting that any effect from this region on tumour production is attributable to the c.3920T>A allele. Our findings further suggest the only somatic genetic change clearly attributable to the c.3920T>A mutation is the c.3924_3925insA.